Threat and Risk Analysis at the Directorate General of Customs and Excise (DJBC) From Intelligence Perspective - Samuel Hartawijaya K; Arthur Josias Simon Runturambi; Thomas Sunaryo (Budapest International Research and Critics University, 2022)
Customs-Excise duties and functions are very vital in maintaining the country's economic resilience. At the same time, customs and excise also cannot be separated from the many threats and risks that can harm the customs and excise agency as an organization (Direktorat Jendral Bea dan Cukai/ DJBC) and as a country. Using mixed methods, this study conducted a survey of 400 member/employee respondents to maping threats and risks in the era of globalization and digitalization. While interviews from 4 sources in the field of customs and excise as qualitative data. The results of this study indicate that the highest threats include smuggling (physical and administrative), resistance to DJBC officers, trade-based money laundering and trans-national organized crime. The existing threats are very risky to the DJBC function related to revenue collection, trade facilitation, industrial assistance and community protection.